ANALISIS KEMAMPUAN PELAYANAN JARINGAN JALAN LINTAS TIMUR PROVINSI ACEH BERDASARKAN INDIKATOR INDEKS PRASARANA JALAN (IPJ) - Liza Karmina; Renni Anggraini; Muhammad Isya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: The national road section of East Aceh Province is the primary road network that connects between the North Sumatra Province and Aceh provincial capital. As the access of Acehnese people to North Sumatra Province is Increasing during the time. Bireuen and Aceh Utara districts are the two districts that crossed by the national roads, this road section is the busiest streets from East section road. To be related with the important role of the national road network of Aceh province, it’s led to the issues of how the road network service capabilities using an indicator of Road Infrastructure Index (IPJ). The purpose of this study is to analyze the ability of the network service by using IPJ indicator. Data collection for indicators of IPJ is by interview to some key informant. Analysis of the IPJ is using four (4) variables: availability of road (Ktj), the performance of the road (Knj), the traffic load (Bln), and the road serviceability (Pyp). The results of analysis IPJ value in 2014 in the district of Bireuen is 1.01 and for North Aceh regency is 0.54, which is the value it’s below the national average score, the score for national is 5.68. The observation from both districts was obtained that total length of the national road network is very poor in serving the number of vehicles and population, but the availability of the national roads in the district has been able to service the administration areas, although the level of the service of road network is very lacking in serve for the daily activities of the population. Abstrak: Ruas jalan nasional Lintas Timur (Lintim) Provinsi Aceh merupakan jaringan jalan primer yang menghubungkan antar ibukota Propinsi Aceh dan Sumatera Utara. Akses pergerakan masyarakat Aceh menuju Provinsi Sumatera Utara semakin hari semakin meningkat. Kabupaten Bireuen dan Aceh Utara adalah dua kabupaten yang dilintasi oleh jalan nasional yang merupakan ruas jalan dengan aktivitas yang cukup padat. Berkaitan dengan pentingnya peranan jaringan jalan nasional Lintim Provinsi Aceh ini, maka muncul permasalahan bagaimana kemampuan pelayanan jaringan jalan Lintim dengan menggunakan indikator Indeks Prasarana Jalan (IPJ). Tujuan dari penelitian ini yaitu menganalisa kemampuan pelayanan jaringan jalan dengan menggunakan indikator IPJ. Pengumpulan data untuk indikator IPJ dilakukan dengan cara wawancara kepada beberapa responden. Analisa terhadap IPJ menggunakan 4 (empat) variabel yaitu ketersediaan jalan (Ktj),kinerja prasarana jalan(Knj),beban lalu lintas(Bln),dan pelayanan prasarana jalan (Pyp). Dari hasil analisis diperoleh nilai IPJ pada tahun 2014 di Kabupaten Bireuen = 1,01 dan Kabupaten Aceh Utara = 0,54 dimana nilai tersebut jauh dibawah skor rata-rata nasional yaitu 5,68. Pada kedua kabupaten yang diamati diperoleh panjang total jaringan jalan nasional masih sangat kurang dalam melayani jumlah kenderaan dan jumlah penduduk, namun ketersedian jalan nasional yang ada di kabupaten ini sudah mampu memberi akses untuk melayani daerah adminitrasinya, walaupun dengan tingkat pelayanan jaringan jalan masih sangat kurang dalam melayani aktivitas penduduk sehari-hari.